Nutritional Value of a Commercial Flathead Fish Species (Platycephalus indicus) from Karachi Waters, Pakistan - Shamsan, Ebtisam F.; Ahmed, Shakil; Khatoon, Nasima; Ghoran, Salar Hafez (PSM Biological Research, 2025)
Many fish species are commonly used as food by local communities but are not attracting researchers to investigate their nutritional benefits. From this point of view, this study aimed to investigate the nutritional value of a commercial fish species, Platycephalus indicus, which is sold at moderately low prices in Karachi, Pakistan. The investigation was carried out using standard AOAC official methods of analysis to determine the major constituents of food that reflect its nutritional value for humans. The results revealed high values of moisture (73.09 ± 1.38%), protein (23.19 ± 2.12%), and ash (4.25 ± 0.13%), but low values of fat in the muscle of this fish. The muscle was also mixed with skin and analyzed for the mentioned components; the results were not significantly different from that found in the muscle: 72.03± 1.62%, 22.39± 0.88%, and 4.21± 0.33% for moisture, protein, and ash, respectively. The fat content was the only constituent that showed a significant difference, with 1.44 ± 0.52% for muscle and 2.76 ± 0.90% for the muscle mixed with skin (P<0.05). The caloric value indicates the validity of this fish as a healthy food.